Flood Simulation Using HEC-RAS for Sg Suloh, Batu Pahat. - YAP, CHEE KEONG; MOHD YUSOFF, MOHD AZLAN (Recent Trends in Civil Engineering and Built Environment, 2022)
Flooding is one of the actions on water on overflowing from the water source onto land which is normally dry and river flooding that mentioning in this article journal is about the overflowing of water from the river onto the dry land and flooding has caused some issues on economy and social aspect in one country. Hence, the Flood Inundation is carried out for identify the risk so that the damage can be reduce after the alternative solution is further discussed and carried out. The HEC-RAS model is being applied in this research as it can fulfil the objective of this research. The objective of this research is to identify the river conveyance capacity and generating the flood inundation map by using HEC-RAS model to examine risk of flooding along the Sg Suloh, Batu Pahat as that area is a flooding zone with the consideration of probability of flood repeat occurrence period, which also mentioned as return period. Before the use of the software for simulating the flooding of the region, some input data are required such as topography data, Manning’s roughness coefficients (n) and the flow data which consists of flow rate, boundary conditions and other consideration that need to be included. By inputting these data, the HEC-RAS model will simulate the flow conditions on steady and unsteady states as the simulation is based on standard step by step numerical methods to calculate the water surface elevation between the required periods. Furthermore, the method used is applied according to the relationship in terms of energy that initializing the calculation on flow downstream.